KECERDASAN EMOSIONAL, KOMITMEN ORGANISASI, DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR TERHADAP KINERJA PEGAWAI BANK PERSERO - HENDRA DARMAWAN; YUPITER GULO (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2019)
The purpose of this research is to examine the influence and relationship of performance base on three influence such as emotional intelligent, organizational commitment, and organizational citizenship behavior of PT. Bank Mandiri (Persero) Tbk. Cluster area Bekasi Juanda-1. The methods which is used in the research is descriptive and causality respondents involved in this study as many as 75 people. The study used saturated sampling. The data collection is done by spreading questionnaire. And the method for the data analysis in this research is regression which are multiple linear regression using the Statistical Package for Social Science (SPSS) version 24. The result of this research is, emotional intelligent and organizational citizenship behavior has an impact to performance but organizational commitment have no impact to performance.